Yes to cataloguing - but how? - Peset, Fernanda; Baiget, Tomí s (Anuario ThinkEPI, 2008)
A paradigm shift is taking place in cataloguing codes. After the massive success of simple information retrieval systems like Google, some cataloguers are calling for a simplification of document descriptions. CoyleÂ and HillmannÂ criticize the AACR update because of the excessive weight given to library traditions in the work that is underway.